Exploring the changes in the field of HRM - Hua, Weiwei (2007)
Abstract Human resource management (HRM) involves the administration of employees to achieve managers objectives. It is different from traditional resource management that originated in the USA and have adopted in the UK. However, according to Frege's (2005) study, the academic interests outside the UK and US, and the increase of global academic cooperation (e.g. joint publications by authors from different national institutions, international conferences), there are some changes of HRM issues in the 21st century compared with that in the early 1990s. Hence, the objective of this dissertation is to explore the main changes in the field of HRM focusing on the research patterns and content of topics. Also, it aims to examine the recent tendency of HRM research towards internationalization. First of all, it reviews the literatures, outlining the background, key areas and the relevant changes of HRM, reviewing Frege's (2005) previous work and the issue of international human resource management (IHRM). By employing the quantitative research method, the study collects information and data from the articles published in one of the mainstream HRM journals the International Journal of Human Resource Management between 1990-1992 and 2006. Based on the analysis and discussion of the results, the dissertation traces the changes in the field of HRM, finding main changes both in researchn patterns (the nature and the content of articles) and in the key areas of HRM.Moreover, it examines the future tendency of HRM development towards internationalization.